(untitled) (Zien Journal of Social Sciences and Humanities, 2022)
The study examined the effect of marketing attributes of Visitor Attractions (VAs) (activities and support services) on tourists’ destination loyalty in the tourism industry of Port Harcourt, Rivers State, Nigeria. The descriptive survey research generated primary data from a sample of 100 tourists/visitors who patronised the VAs selected for the study using a well-structured questionnaire made up of nine items, with five demographic items. Inferential statistics was conducted with the help of Statistical Package for Social Science (SPSS) to validate the four hypothesised relationships. The statistical results of the inferential statistical analysis revealed that support services had direct positive significant effect on tourists destination loyalty, while activities did not have significant effect on destination loyalty. The study concluded that support services constitute an important marketing attribute that determines the loyalty of tourists to a particular destination for touristic purposes. It is recommended that entrepreneurs managing VA should identify, evaluate and collaborate with tourism service providers providing support services at their sites based on their target market needs. Academic and practitioners’ implications are provided